Pengaruh Minuman Larutan Air Gula Merah Terhadap Recovery Denyut Nadi Pada Atlet Futsal Putri - Khairiyyah, Muthiah; Imanudin, Iman; Haryono, Tono; Zaky, Mohammad (Dharmas Journal of Sport, 2025)
This study aims to analyze the effect of giving brown sugar water solution drinks on the pulse recovery of female futsal athletes. This study uses an experimental method with one group pre test post test. The sample was 20 female futsal athletes of the amateur club futsal d'ningrum team using the random sampling method. Researchers will compare the difference in athlete pulse recovery time with the pre test only given plain water while the post test is given a brown sugar solution drink. recovery time is measured by palpation. Statistical tests using spss version 23, the results obtained that the paired t test gets a value of 0.000, this means shows that there is a significant effect of giving brown sugar solution drinks on pulse recovery in female futsal athletes. This is also indicated by the average pulse recovery time which is faster in giving brown sugar water solution drinks compared to plain water.